The European species of Foersterella Dalla Torre (Hymenoptera: Tetracampidae), including the description of two new species - Hansson, Christer (Zootaxa, 2016)
The European species of Foersterella Dalla Torre 1897 (Hymenoptera: Tetracampidae) are treated, including two previously described species, F. erdoesi Bouček and F. reptans (Nees), and two new species, F. angusticornis sp. nov. and F. fuscicornis sp. nov. Morphological concepts of the species are based mainly on characters in the male antenna, which females lack, and with the exception of F. erdoesi females are currently not possible to identify to species. A key for the identification of species is included, as well as illustrations to facilitate the identification.